2020
DOI: 10.3389/fcell.2020.00002
|View full text |Cite
|
Sign up to set email alerts
|

ATR-Mediated FANCI Phosphorylation Regulates Both Ubiquitination and Deubiquitination of FANCD2

Abstract: DNA interstrand crosslinks (ICLs) are a physical barrier to replication and therefore toxic to cell viability. An important mechanism for the removal of ICLs is the Fanconi Anemia DNA repair pathway, which is initiated by mono-ubiquitination of FANCD2 and its partner protein FANCI. Here, we show that maintenance of FANCD2 and FANCI proteins in a monoubiquitinated form is regulated by the ATR-kinase. Using recombinant proteins in biochemical reconstitution experiments we show that ATR directly phosphorylates FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 44 publications
(63 reference statements)
2
35
0
2
Order By: Relevance
“…The FANCD2-FANCI heterodimer, frequently called the central complex, is recruited to the stalled fork, where FANCI is tri-phosphorylated by the ATR-kinase [ 15 ], stimulating the FA core complex mediated monoubiquitination of both FANCI and FANCD2. The tri-phosphorylation of FANCI also inhibits the deubiquitinase activity of the USP1-UAF1 complex over the ID2 complex until ICL repair and replication are completed [ 15 ]. The ubiquitinated ID2 complex protects the replication forks and regulates the activity of the proteins involved in the processing of the ICL, enabling the recruitment of the proteins of the fourth module.…”
Section: Double Strand Breaks Are At the Center Of Chromosome Abermentioning
confidence: 99%
“…The FANCD2-FANCI heterodimer, frequently called the central complex, is recruited to the stalled fork, where FANCI is tri-phosphorylated by the ATR-kinase [ 15 ], stimulating the FA core complex mediated monoubiquitination of both FANCI and FANCD2. The tri-phosphorylation of FANCI also inhibits the deubiquitinase activity of the USP1-UAF1 complex over the ID2 complex until ICL repair and replication are completed [ 15 ]. The ubiquitinated ID2 complex protects the replication forks and regulates the activity of the proteins involved in the processing of the ICL, enabling the recruitment of the proteins of the fourth module.…”
Section: Double Strand Breaks Are At the Center Of Chromosome Abermentioning
confidence: 99%
“…The FANCD2-FANCI heterodimer, frequently called the central complex, is recruited to the stalled fork, where FANCI is tri-phosphorylated by the ATRkinase [15], stimulating the FA core complex mediated monoubiquitination of both FANCI and FANCD2. The tri-phosphorylation of FANCI also inhibits the deubiquitinase activity of the USP1-UAF1 complex over the ID2 complex until ICL repair and replication are completed [15]. The ubiquitinated ID2 complex protects the replication forks and regulates the activity of the proteins involved in the processing of the ICL, enabling the recruitment of the proteins of the fourth module.…”
Section: Involvement Of Fa/brca Pathway In Dna Repairmentioning
confidence: 99%
“…In addition, the β-propeller domain of UAF1 interacts with a loop connecting the NTD and HD of FANCI (FANCI 547-576 ), the phosphorylation of which inhibits deubiquitination by USP1-UAF1 28,29 ( Fig. 3a).…”
Section: Uaf1 and Fanci Form A Scaffold For Deubiquitinationmentioning
confidence: 99%
“…Furthermore, FANCI buries a substantial surface of FANCD2's ubiquitin 15,16 , which shields it from several deubiquitinases but not USP1-UAF1 in vitro 18 . Instead, FANCI phosphorylation is reported to impede USP1-UAF1 activity 28,29 ; the underlying mechanism of this regulation remains unclear. Recently, biochemical work has shown that the NTE of USP1 is critical for specific removal of FANCD2's ubiquitin 20 .…”
Section: Introductionmentioning
confidence: 99%